PERANCANGAN STANDARD OPERATING PROCEDURE (SOP) ROTI SOBEK PADA UMKM ROTI SS DI KABUPATEN JEMBER - Alto Agung Prasasti; Paramita Andini; R. Abdoel Djamali; Andi Muhammad Ismail (LPSDI Bina Patria, 2025)
Due to the lack of a defined and organized Standard Operating Procedure (SOP), Roti SS now confronts considerable hurdles in its tear-off bread production processes. There is a lack of clear direction at every level of production due to manufacturing methods that still mostly rely on verbal instructions and ingrained habits. Consequently, the process's efficiency is hindered and the employees' performance is subpar. The first goal of this study is to fully identify every step in the MSME Roti SS torn bread production process in order to address these issues. Second, create thorough and suitable SOPs for every one of these phases. Third, assess how well the SOPs that have been created and put into place are working. In order to fully comprehend and address issues with product quality and operational efficiency in SS Bread MSMEs in Jember, this study combines descriptive qualitative and quantitative methodologies. According to the study's findings, MSME Roti SS's quality and operational efficiency have improved as a result of the design of SOPs at every step of the torn bread production process and the successful implementation of these procedures, which is demonstrated by a notable drop in defective products. It was observed that the SOP's application was able to cut the quantity of defective goods produced in a single procedure by 14%. Employees still need to adapt their personal protective equipment (PPE) when using SOP.